2017
DOI: 10.3851/imp3199
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Decreases Immune Activation and Exhaustion in HIV-1-Infected Youth

Abstract: Vitamin D supplementation decreased markers of T-cell activation/exhaustion and monocyte activation in HIV-infected youth, with subjects given the highest dose (120,000 IU/month) showing the greatest decreases. These data suggest that high-dose vitamin D supplementation may attenuate immune activation and exhaustion, and serve as adjuvant therapy to antiretroviral therapy in HIV. ClinicalTrials.gov identifier: NCT01523496.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 30 publications
0
34
0
6
Order By: Relevance
“…reported that plasma 25(OH)D levels were significantly positively correlated with CD4 + T‐cell counts after 24 weeks of VitD supplementation and that each 1.0 ng/ml increase in 25(OH)D during repletion therapy was associated with a 3.3 cell/µl increase in the CD4 + T‐cell count . Although others have found that VitD supplementation is associated with reduced immune activation and CD4 + T‐cell exhaustion levels, it has no effect on CD4 + T‐cell recovery in both untreated and treated HIV‐1‐infected individuals . Therefore, additional investigation is needed to determine whether VitD can promote immune reconstitution.…”
Section: Intervention Measures For Poor Immune Reconstitutionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported that plasma 25(OH)D levels were significantly positively correlated with CD4 + T‐cell counts after 24 weeks of VitD supplementation and that each 1.0 ng/ml increase in 25(OH)D during repletion therapy was associated with a 3.3 cell/µl increase in the CD4 + T‐cell count . Although others have found that VitD supplementation is associated with reduced immune activation and CD4 + T‐cell exhaustion levels, it has no effect on CD4 + T‐cell recovery in both untreated and treated HIV‐1‐infected individuals . Therefore, additional investigation is needed to determine whether VitD can promote immune reconstitution.…”
Section: Intervention Measures For Poor Immune Reconstitutionmentioning
confidence: 99%
“…217 Although others have found that VitD supplementation is associated with reduced immune activation and CD4 + T-cell exhaustion levels, it has no effect on CD4 + T-cell recovery in both untreated and treated HIV-1-infected individuals. [218][219][220] Therefore, additional investigation is needed to determine whether VitD can promote immune reconstitution.…”
Section: -Infected Individuals Receiving the Dolutegravir-abacavir-lmentioning
confidence: 99%
“…After 12 months of supplementation, 25(OH)D increased from 17 (11, 21) ng/mL to 31 (22, 37) ng/mL in the control group and from 18 (14, 22) ng/mL to 42 (33, 53) ng/mL in the combined medium and high dose groups (within and between groups p<0.001), but there were no differences between groups in changes in BMD or bone markers(80**). Notably, supplementation decreased markers of T-cell activation and exhaustion and monocyte activation regardless of the dose; although, participants given the highest dose showed the greatest improvements(81). Collectively, these studies suggest that there is a role for vitamin D supplementation in HIV-infected patients initiating ART and while undergoing treatment with alendronate for low BMD, but the effect of supplementation outside of these two settings is unclear.…”
Section: Vitamin D and Bone In Hivmentioning
confidence: 99%
“…Studies about vitamin D supplementation in HIV-positive populations have been conducted [ 6 14 ]. However, indirect comparisons of these studies lead to equivocal conclusions, while direct comparative studies are limited [ 15 , 16 ]. As HIV infection itself as well as different antiretroviral drugs significantly influence bone, calcium, and vitamin D metabolism [ 17 ], it is unclear whether the results of previous studies about the dosing regimens of cholecalciferol supplementation in general populations apply to PLWH.…”
Section: Introductionmentioning
confidence: 99%